Acylation of Arylamines with Triethylamine Derivatives in Combination with tert‐Butyl Hydroperoxide. Issue 4 (29th March 2019) - Chen, Cui; Liu, Weibing.; Liu, Bifu.; Zhou, Peng; Tan, Hua
Abstract: N‐acylation of arylamines with di‐ and trialkyl amines has been reported. This approach provides a general synthesis of aromatic amides by an alkyl transfer through cleavage of the C−N bond, and acts as a model for N‐dealkylations and N‐acylations. Additionally, the synthesis is a promising method towards amidation reactions, wherein di‐ and trialkyl amine derivatives are employed as sources of acyl carbon atoms and tert ‐butyl hydroperoxide is employed as the oxygen source of the acyl group. Abstract : This protocol affords N‐acylation of arylamines with di‐ and trialkyl amines. The method provides a general synthesis of aromatic amides via an alkyl transfer through cleavage of the C−N bond.